Method for preparing high-hydrophobicity microporous carbon through low-temperature plasma anchoring oxygen-containing functional group assisted ion exchange

Through the low-temperature plasma anchoring oxygen-containing functional group auxiliary ion exchange method, the problems of high-temperature calcination and use of strong corrosive reagents were solved, and high-hydrophobic microporous carbon that efficiently adsorbs volatile organic compounds was prepared, realizing green and simple processes and Highly efficient adsorption effect.

CN119236878APending Publication Date: 2025-01-03HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411002474.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art has problems such as high-temperature calcination, use of strong corrosive reagents and low yields in the preparation of high-hydrophobic microporous carbon, making it difficult to achieve a green, simple and effective process.

Method used

Using the low-temperature plasma anchored oxygen-containing functional group auxiliary ion exchange method, the biological carbon source is treated with low-temperature plasma, mixed with alkali metal hydroxide and high-temperature carbonization, to form a highly hydrophobic micro-micro with uniform pore size distribution and orderly pore structure. Porous charcoal.

Benefits of technology

It effectively reduces the use of chemical activation reagents, avoids the negative impact of strongly corrosive chemical reagents, and prepares extremely microporous and highly hydrophobic biochar adsorbents that are highly effective in adsorbing volatile organic compounds, and is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236878A_ABST
    Figure CN119236878A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of porous materials, and provides a method for preparing high-hydrophobicity microporous carbon through low-temperature plasma anchoring oxygen-containing functional group assisted ion exchange, which comprises the following steps: (1) carrying out low-temperature plasma treatment on a biological carbon source to obtain a surface modified material; (2) mixing the surface modified material with alkali metal hydroxide to obtain an alkali metal-surface modified material; (3) carrying out high-temperature carbonization treatment on the alkali metal-surface modified material under the condition of 800-1000 DEG C; the low-temperature plasma treatment comprises the step of treating the biological carbon source by using low-temperature plasma under the air atmosphere and the voltage of 30-60kV. The preparation process disclosed by the invention is simple, and the prepared electrode-rich micropore high-hydrophobicity biochar adsorbent is uniform in pore size distribution, ordered in pore structure and good in adsorption effect on volatile organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous materials, and more specifically to a method for preparing highly hydrophobic microporous carbon by low-temperature plasma anchoring oxygen-containing functional groups and assisting ion exchange. Background Art

[0002] Volatile organic compounds (VOCs) are toxic and carcinogenic, causing environmental pollution and threatening human health. With the acceleration of industrialization and economic growth, the emission of VOCs has increased dramatically. Among the technologies used to remove VOCs from the environment, adsorption technology is considered to be an effective way to control VOCs pollution. It can enrich VOCs and release them from the adsorbent in an appropriate manner, thereby realizing the recycling of VOCs and the regeneration of adsorbents. The adsorption method has the advantages of high cost-effectiveness, flexible operation, and low energy consumption, and is considered to be one of the most promising recovery technologies. Adsorption is divided into physical adsorption and chemical adsorption. Physical adsorption is mainly affected by pore size, among which macropores contribute to the exposure of pores, mesopores contribute to the enhancement of the diffusion of VOCs, and micropores are the main adsorption sites of VOCs. By controlling the pore structure, hydrophobic sites, π-electron structure, and surface functional groups, adsorbents with specific structures can be designed for the adsorption of aromatic VOCs. Porous carbon as an adsorbent has attracted more and more attention. During the adsorption process, the accessibility of adsorbed VOCs can be adjusted by adjusting the pore structure. Currently, adsorbents that adsorb a large amount of VOCs are easily affected by humidity. Therefore, the development of hydrophobic materials with high specific surface area and a large number of regular micropore structures is helpful for the adsorption of VOCs.

[0003] Currently, zeolites, carbon-based materials, and organic polymers are widely used as adsorbents due to their wide surface area and considerable pore volume. However, these commonly used adsorbent materials have yet to be studied and developed in terms of adsorption capacity, hydrophobicity, thermal properties, etc., and the large-scale production and use of these materials pose great challenges, including cost and potential environmental pollution. It is understood that biomass-derived porous carbon materials have the advantages of light weight, large specific surface area, low cost, and good sustainability. The use of biomass can largely reduce the dependence on non-renewable porous carbon precursors.

[0004] Direct carbonization of biomass usually produces carbon materials with low surface area and irregular porosity. By applying an additional activation step, the development of porosity and performance are improved to a certain extent. However, the process usually requires harsh conditions, including the use of corrosive reagents, high-temperature calcination, etc., which is not in line with the principles of green chemistry. Therefore, it is challenging to prepare highly porous carbon directly from biomass or using mild synthesis conditions. The Chinese patent "A method for preparing extremely porous carbon materials based on carboxylation anchoring" (CN112340730B) provides a method for introducing alkali metals into the surface of the material by using alkali and carboxyl ion exchange, and fixing alkali metal ions in specific positions by the anchoring effect of carboxyl groups. The patent uses an impregnation method to introduce carboxylic acids and alkali metals. The entire modification cycle is long, the yield is low, and it is not convenient for industrial application. Therefore, it is urgent to develop a new simple, clean and efficient modification method. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing highly hydrophobic microporous carbon by low-temperature plasma anchoring oxygen-containing functional groups assisted by ion exchange. The present invention can effectively reduce the amount of chemical activation reagents used and reduce the negative impact of consuming a large amount of highly corrosive chemical reagents in the activated carbon preparation process. The preparation process is simple, and a highly hydrophobic biochar adsorbent with rich micropores and uniform pore size distribution, ordered pore structure and good adsorption effect on volatile organic compounds is prepared.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing highly hydrophobic microporous carbon by low-temperature plasma anchoring oxygen-containing functional groups and assisting ion exchange, comprising:

[0008] (1) treating the biocarbon source with low-temperature plasma to obtain a surface-modified material;

[0009] (2) mixing the surface modification material with an alkali metal hydroxide to obtain an alkali metal-surface modification material;

[0010] (3) subjecting the alkali metal-surface modified material to high temperature carbonization treatment at 800-1000°C;

[0011] The low temperature plasma treatment comprises:

[0012] The biocarbon source is treated with low-temperature plasma in an air atmosphere at a voltage of 30 to 60 kV.

[0013] Preferably, the biocarbon source comprises waste biomass rich in cellulose, hemicellulose and lignin from agriculture, forestry and gardening, preferably rice husk.

[0014] The present invention uses rice husks, an agricultural and sideline product with abundant production in China, as raw materials. The prepared carbon adsorbent has the advantages of light weight, large specific surface area, low cost, good sustainability, etc. The use of biomass can greatly reduce the dependence on non-renewable porous carbon precursors, realize the resource utilization of solid waste, and solve certain social, economic and scientific problems.

[0015] Preferably, the time of the low-temperature plasma treatment is 5 to 25 minutes; the relative humidity of the low-temperature plasma treatment is 50% to 100%; and the discharge current of the low-temperature plasma treatment is 2.0 to 2.3A.

[0016] Preferably, the mass of the biomass raw material treated with low-temperature plasma each time is 1 to 1.2 g.

[0017] Using low temperature plasma (NTP) modification, this method avoids the environmental and ecological problems caused by strong acid and strong base pore formation, and is more in line with the concept of green chemistry. The two mechanisms of NTP modification are physical modification mechanism: high voltage current bombards the air to generate discharge and acts on the material surface, causing the material surface to be etched, thereby achieving the purpose of pore formation; chemical modification mechanism: high voltage current bombards the air and the material surface, and the O2 molecules, N2 molecules and H2O molecules in the air are bombarded by the current and become a large number of active ions (O - 、N - OH - ), these active ions interact with the material surface, enriching the material surface with oxygen-containing functional groups.

[0018] Preferably, before the low-temperature plasma treatment, the biocarbon source is pretreated; the pretreatment includes: crushing the biocarbon source and / or removing impurities; the crushing includes: the removal of impurities includes: mixing the biocarbon source with an acid, reacting at 50-60°C for 1-2h, and drying; the acid includes a protonic acid, preferably hydrochloric acid, more preferably 1-1.5 mol / L hydrochloric acid; the liquid-to-solid ratio of the biocarbon source and the acid is 6:(20-25) g / ml; the drying temperature is 50-100°C, and the time is 6-48h; the drying is preferably carried out in a blower.

[0019] Preferably, the mixing of the surface modification material and the alkali metal hydroxide is carried out at 50-150° C.; the alkali metal oxide is mixed with the surface modification material in the form of a solution for 0.5-2.5 hours; in the alkali metal oxide solution, the concentration of the alkali metal oxide is 0.5-2 mol / L, preferably 2 mol / L; the material-liquid ratio of the surface modification material to the alkali metal oxide solution is 1:(10-15) g / ml, preferably 1:10 g / ml.

[0020] Preferably, the alkali metal hydroxide is one or more of KOH, NaOH, LiOH, and CsOH, preferably KOH.

[0021] Preferably, after the surface modification material is mixed with the alkali metal hydroxide, the excess alkali is removed by washing with water until it becomes neutral and then dried.

[0022] The present invention uses alkali metal hydroxide as an ion exchanger to anchor alkali metal ions to the surface of the material through ion exchange. After NTP modification, it is treated with alkali metal hydroxide to achieve H bond between alkali metal ions and oxygen-containing functional groups of the material. + Exchange positions to achieve the anchoring effect of oxygen-containing groups.

[0023] Preferably, the high temperature carbonization treatment includes:

[0024] In a N2 atmosphere, the temperature was raised to 800-1000°C at a heating rate of 5°C / min and maintained at 800-1000°C for 60-80 min.

[0025] During the high-temperature calcination process, a series of chemical changes occur between the alkali metal ions anchored on the surface of the material and the components of the material, generating CO2, CO, alkali metal ions, etc., which expand pores inside the material and eventually form highly hydrophobic microporous carbon, that is, highly hydrophobic microporous carbon adsorbent.

[0026] The invention also provides highly hydrophobic microporous carbon prepared by the method.

[0027] The present invention uses low-temperature plasma to anchor oxygen-containing functional groups to assist ion exchange in preparing highly hydrophobic microporous carbon. The present invention uses biomass waste as raw material, and utilizes low-temperature plasma (NTP) technology to rapidly graft a large number of oxygen-containing functional groups onto the material in room temperature air, greatly shortening the surface modification cycle of the material; then, the surface modified material is subjected to ion exchange in an alkali metal hydroxide by an impregnation method; subsequently, the material is subjected to high-temperature carbonization treatment, so that the alkali metal ions anchored on the surface of the material undergo a series of chemical changes with the components of the material, the cellulose, hemicellulose, etc. in the biomass waste are cracked and converted into combustible gases, and a large number of oxygen-containing groups on its surface are broken, releasing CO2, CO, K +Ions, etc., expand pores inside the material, and finally form activated carbon with extremely uniform micropores. In order to evaluate its performance in adsorbing VOCs, the present invention takes 0.1g / L highly hydrophobic microporous carbon NTP-KC-CRH for adsorption experiment in the experimental example, and the adsorption rate of 26.227mg / L PX can reach 98.4% within 60min. In addition, the experiment shows that the adsorption effect of NTP-KC-CRH on PX is not affected by humidity, that is, the present invention obtains a hydrophobic biomass adsorbent with a contact angle of 110.8° (>90°). In a high humidity environment, water molecules gather on the surface of the material, the macropores are partially blocked, the pore size becomes smaller, and it is easier to reach dynamic adsorption equilibrium during adsorption.

[0028] Compared with the traditional method of preparing high-porosity activated carbon by chemical activation, the present invention can effectively reduce the amount of chemical activation reagents used and reduce the negative impact of consuming a large amount of highly corrosive chemical reagents during the preparation of activated carbon. The preparation process is simple, and more importantly, it can prepare a highly hydrophobic biochar adsorbent with uniform pore size distribution, orderly pore structure and good adsorption effect on volatile organic compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 :(a) is the scanning electron micrograph of CRH;(b) is the scanning electron micrograph of NTP-CRH;(c) is the scanning electron micrograph of KC-CRH;(d) is the scanning electron micrograph of NTP-KC-CRH;

[0030] Figure 2 The bar graph is a graph showing the adsorption capacity of p-xylene by the materials obtained in the embodiment, comparative example and experiment 3;

[0031] Figure 3 This is a hydrophobic experimental diagram of highly hydrophobic microporous carbon of Example 1;

[0032] Figure 4 This is the bar graph of the adsorption capacity of p-xylene by the material obtained in Experiment 7;

[0033] Figure 5 This is the bar graph of the adsorption capacity of p-xylene by the material obtained in Experiment 8;

[0034] Figure 6 This is the bar graph of the adsorption capacity of p-xylene by the material obtained in Experiment 9;

[0035] Figure 7 The figure is a bar graph showing the adsorption capacity of the material obtained in Example 1 for different volatile organic compounds. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In order to further illustrate the present invention, the following examples are used to explain it in detail. The raw materials used in the following examples and comparative examples of the present invention are all commercially available products.

[0038] 1. Implementation

[0039] Example 1

[0040] The method for preparing highly hydrophobic microporous carbon (NTP-KC-CRH) by low-temperature plasma anchoring oxygen-containing functional groups assisted by ion exchange in this embodiment comprises the following steps:

[0041] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0042] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0043] (3) The pretreated rice husk powder was placed in an air dielectric barrier discharge (DBD) low temperature plasma (NTP) modification device, and the discharge voltage was 40 V, the discharge current was 2.0 A, and the discharge time was 10 min under an air relative humidity of 100%. Through the NTP treatment, the surface of the rice husk powder was etched, and a large number of oxygen-containing groups (-COOH, -C=O, -OH) were introduced into the surface.

[0044] (4) At a temperature of 80°C, 5 g of the surface modified material was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring effect of the oxygen-containing groups. The material was then washed with water to remove excess alkali until it was neutral, and then dried in a forced air drying oven at 80°C.

[0045] (5) The dried material was placed in a tubular furnace, heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 800 °C for 60 min for carbonization. After naturally cooling to room temperature, the black highly hydrophobic microporous carbon NTP-KC-CRH was finally obtained.

[0046] Comparative Example 1

[0047] The preparation method of the carbon adsorbent (KC-CRH) obtained by simple ion exchange in this comparative example is different from that in Example 1 only in that the low-temperature plasma treatment process is omitted in this comparative example, and comprises the following steps:

[0048] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0049] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0050] (3) At a temperature of 80°C, 5 g of rice husk powder was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring of oxygen-containing groups. The excess alkali was then removed by washing with water until it was neutral, and then dried in a forced air drying oven at 80°C.

[0051] (4) The dried material was placed in a tubular furnace, heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 800 °C for 60 min for carbonization. After naturally cooling to room temperature, the black rice husk carbon adsorbent KC-CRH was finally obtained.

[0052] Comparative Example 2

[0053] The simple NTP modified carbon adsorbent (NTP-CRH) of this comparative example is different from Example 1 only in that the KOH solution impregnation process is omitted in this comparative example, and comprises the following steps:

[0054] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0055] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0056] (3) The pretreated rice husk powder was placed in an air dielectric barrier discharge (DBD) low temperature plasma (NTP) modification device, and the discharge voltage was 40V, the discharge current was 2.0A, and the discharge time was 10min under an air relative humidity of 100%. Through NTP treatment, a rice husk powder with an etched surface and a large number of oxygen-containing groups (-COOH, -C=O, -OH) introduced into the surface was obtained.

[0057] (4) The surface modified material was placed in a tubular furnace, heated to 800°C at a heating rate of 5°C / min under a N2 atmosphere, and maintained at 800°C for 60 min for carbonization. After naturally cooling to room temperature, the black rice husk carbon adsorbent NTP-CRH was finally obtained.

[0058] Comparative Example 3

[0059] The direct activated carbon adsorbent (CRH) of this comparative example is different from Example 1 only in that the low-temperature plasma treatment process and the KOH solution impregnation process are omitted in this comparative example, and comprises the following steps:

[0060] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0061] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0062] (3) The dried material was placed in a tubular furnace, heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 800 °C for 60 min for carbonization. After naturally cooling to room temperature, the black rice husk carbon adsorbent CRH was finally obtained.

[0063] 2. Experimental Examples

[0064] Experiment 1

[0065] The specific surface area and pore structure of CRH (Comparative Example 3), NTP-CRH (Comparative Example 2), KC-CRH (Comparative Example 1) and NTP-KC-CRH (Example 1) prepared in the examples and comparative examples were tested and analyzed. The results are shown in Table 1. Since rice husk contains a large amount of cellulose and lignin, its overall morphology is long and fibrous, with a large number of macropores on the side and uniform micropores on the inner wall of the pores. The pore size of the macropores is conducive to the exposure of the pores and is more conducive to the transmission of the adsorbed substrate; the more micropores there are, the larger the specific surface area is, which is conducive to the distribution of active sites and increases the contact between the active sites and the adsorbed substrate. + The specific surface area increased significantly after exchange, and the specific surface area of ​​CRH obtained by direct activation without treatment was 341.1056m 2 g -1 , while the specific surface area of ​​NTP-KC-CRH increased to 644.2062m 2 g -1Compared with rice husk charcoal treated with KOH and modified with NTP, the specific surface area and pore volume are increased, and the average pore size of NTP-KC-CRH is 1.7387nm (<2.0nm), accounting for as high as 86.3%. Table 1 records the specific surface area and pore volume of the materials obtained in the embodiments and comparative examples.

[0066] Table 1: Specific surface area and pore volume of rice husk-based carbon adsorbent

[0067]

[0068]

[0069] Experiment 2

[0070] The surface morphologies of CRH (Comparative Example 3), NTP-CRH (Comparative Example 2), KC-CRH (Comparative Example 1) and NTP-KC-CRH (Example 1) prepared in the embodiments of the present invention and the comparative examples were observed using a Verios G4 field emission scanning electron microscope. The results are as follows: Figure 1 As shown in (a)-(d) in the figure, the scanning electron microscope of CRH was observed Figure 1 (a), it can be observed that the morphology of directly carbonized rice husk is fibrous with regular macropores on the side. The SEM image of NTP-CRH is shown in Figure 1 As shown in (b), it can be observed that the surface of the rice husk carbonized after NTP treatment is bombarded with high energy, the large pores are partially collapsed, and the exposed small pores are partially blocked. BET =343.1056m 2 g -1 ; V Total =0.164835cm 3 g -1 ) compared with the specific surface area and pore volume (S BET =368.4338m 2 g -1 ; V Total =0.147577cm 3 g -1 ) are consistent with the results with little difference. Figure 1 (c) It can be observed that the rice husk treated with KOH and then carbonized maintained its original fibrous morphology, with regular macropores on the side, but micropores appeared inside the macropores, which indicates that potassium ions exchanged with a small amount of oxygen-containing functional groups inherent on the surface of the rice husk powder. Finally, after carbonization, the potassium ions melted and the oxygen-containing functional groups were decomposed into gas, achieving the purpose of creating a small amount of micropores, which is consistent with the increase in specific surface area and pore volume (S BET =535.6749m 2 g -1 ; VTotal =0.225247cm 3 g -1 ) is consistent. Observation Figure 1 (d) It can be seen that there are a large number of uniform micropores on the surface of NTP-KC-CRH. This is because the rice husk powder is NTP-modified in the air, and the surface of the rice husk powder is physically bombarded, resulting in the collapse of the surface pores. At the same time, the air is bombarded into high-energy particles (O - 、N - , H + ), high-energy particles and rice husk powder form a large number of oxygen-containing functional groups grafted onto the rice husk powder through chemical reaction, and then undergo potassium ion exchange and carbonization, potassium ions melt into potassium vapor, and a large number of oxygen-containing functional groups decompose into gases (CO2, CO), thereby achieving the purpose of pore formation. A large number of uniform micropores appear on the surface of the obtained NTP-KC-CRH, greatly increasing the specific surface area and pore volume (S BET =644.2062m 2 g -1 ; V Total =0.280026cm 3 g -1 ), which is beneficial to the improvement of the adsorption performance of the material.

[0071] Experiment 3

[0072] The experimental sequence was changed to alkali metal ion exchange first and then NTP modification to explore the rationality of this invention sequence. This experiment set up a comparative experiment, which specifically included the following steps:

[0073] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0074] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0075] (3) At a temperature of 80°C, 5 g of rice husk powder was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring of oxygen-containing groups. The excess alkali was then removed by washing with water until it was neutral and then dried in a forced air drying oven at 80°C.

[0076] (4) The dried material was placed in a tubular furnace, heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 800 °C for 60 min for carbonization. After naturally cooling to room temperature, the black rice husk carbon adsorbent KC-CRH was finally obtained.

[0077] Then KC-CRH was placed in an air dielectric barrier discharge (DBD) low-temperature plasma (NTP) modification device. In an environment with an air relative humidity of 100%, the discharge voltage was 40V, the discharge current was 2.0A, and the discharge time was 10min to obtain the material KC-CRH-NTP.

[0078] To further illustrate the effect of the present invention on improving adsorption performance, at an ambient temperature of 30°C and a relative air humidity of 0%, in a 650mL headspace bottle, volatile organic gas p-xylene (PX 20μL) with a concentration of 26.227mg / L was used as the target pollutant, and the adsorption performance of CRH (Comparative Example 3), NTP-CRH (Comparative Example 2), KC-CRH (Comparative Example 1), NTP-KC-CRH (Example 1) and KC-CRH-NTP were characterized, and the dosage was 0.1g / L. When the adsorption time of gaseous PX was 120min, the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the adsorption of the materials in the embodiments and comparative examples tends to be stable after 80 minutes. At 60 minutes, the removal rates of PX by CRH (Comparative Example 3), NTP-CRH (Comparative Example 2), KC-CRH (Comparative Example 1), NTP-KC-CRH (Example 1) and KC-CRH-NTP are 34.3%, 35.6%, 46.2%, 98.4% and 47.5%, respectively. The removal rate of PX by NTP-KC-CRH in Example 1 of the present invention is significantly higher than that by CRH directly activated, NTP-CRH obtained by simple NTP modified carbon material (without ion exchange process), and KC-CRH obtained by simple KOH ion exchange (without NTP modification process). This shows that by NTP modification, oxygen-containing groups on the surface of the material are first increased, and then KC-CRH is used to remove PX. + The effectiveness of this modification method of anchoring oxygen-containing groups and finally obtaining a uniform microporous rice husk-based carbon adsorbent through high-temperature activation.

[0079] Experiment 4

[0080] In order to further illustrate that the carbon material prepared by the method of the present invention is not easily affected by humidity when adsorbing PX, this experiment selected NTP-KC-CRH prepared from rice husk as the raw material as the test object, and used a pipette to drop liquid at a close distance to evaluate its hydrophobicity (test instrument model: JY-82C; water drop size: 16μL; test method: sessile drop method; angle measurement method: angle measurement method). The test results are as follows Figure 3 As shown, the contact angle of NTP-KC-CRH obtained in Example 1 is 110.8° (>90°), which is a highly hydrophobic material.

[0081] Experiment 5

[0082] Referring to the reported literature, various actual biomasses (corn straw, wheat straw, bamboo, pine and corn cob) were co-activated with (NH4)2C2O4 and KHCO3 to prepare porous carbon for adsorbing VOCs, including the following steps:

[0083] (1) The rice husk is crushed to obtain 80-mesh rice husk powder (RH).

[0084] (2) Mixing raw materials: Rice husk powder, (NH4)2C2O4 and KHCO3 were thoroughly mixed together in a mass ratio of 1:3:1, and the mixture was placed in a ceramic crucible. Then, the ceramic crucible was placed in a temperature-controlled furnace, and the mixture was calcined at 900°C in N2 for 60 min with a heating rate of 10°C / min.

[0085] (3) The calcined product was dissolved in 500 mL of HCl solution (0.5 mol / L) and magnetically stirred at room temperature for 24 h. Then, the solution was filtered and washed with deionized water until the pH value of the filtrate reached 7. Finally, the black residue was dried in an oven at 105 °C overnight to obtain rice husk charcoal N-CRH.

[0086] (4) The rice husk charcoal N-CRH was placed in a 650mL headspace bottle at an ambient temperature of 30°C and a relative humidity of 0%. The volatile organic gas PX with a concentration of 26.227mg / L was used as the target pollutant. The N-CRH dosage was 0.1g / L and the removal rate of PX within 120min was observed. It was found that the adsorption effect reached 94% at 30min.

[0087] This experiment is implemented according to the method proposed in the reference document "Adsorption of multi-component VOCs on various biomass-derived multi-level porous carbons: Study on adsorption mechanism and competitive effect (DOI: org / 10.1016 / j.chemosphere.2022.137513)". This method adopts direct mixing and one-step high-temperature calcination, which greatly shortens the material preparation cycle, and the addition of N elements improves its adsorption effect on PX. However, this method directly puts the chemical reagents into the tube furnace, which has a more obvious corrosive effect on the equipment. In contrast, the present invention uses fewer chemical reagents, and the modification method is green and gentle. The material is washed to neutral before calcination, avoiding corrosion to the tube furnace and related equipment.

[0088] Experiment 6

[0089] The carbon material is prepared by referring to the reported Chinese invention patent with authorization announcement number CN 112340730 B (invention title: A method for preparing a very microporous carbon material based on carboxylation anchoring), which specifically includes the following steps:

[0090] (1) The rice husk is crushed to obtain 80-mesh rice husk powder (RH).

[0091] (2) 10 g of rice husk powder was immersed in 50 mL of 0.6 mol / L citric acid solution for 0.5 h, and then dried in a forced air drying oven at 50 ° C for 24 h. The dried material was reacted at 120 ° C for 90 min, and then the material was washed with water until neutral, and then dried to obtain a carboxylated material.

[0092] (3) At a temperature of 80°C, 5 g of the carboxylated material was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 12 h. The metal ions were evenly distributed on the surface of the material through the anchoring effect of the carboxyl group. The material was then washed with water to remove excess alkali until it was neutral and dried.

[0093] (4) The dried material was placed in a tubular furnace and heated to 800°C at a heating rate of 5°C / min under a N2 atmosphere, and maintained at 800°C for 60 min for reaction. After naturally cooling to room temperature, the obtained black solid was washed with deionized water and then placed in an oven for drying. After drying, the rice husk carbon material CK-CRH was obtained.

[0094] (5) Rice husk charcoal CK-CRH was placed in a 650 mL headspace bottle at an ambient temperature of 30 °C and a relative humidity of 0%. The volatile organic gas PX with a concentration of 26.227 mg / L was used as the target pollutant. The CK-CRH dosage was 0.1 g / L and was placed in a 650 mL headspace bottle. The removal rate of PX within 120 min was observed. It was found that the adsorption effect was only 52.1% at 60 min.

[0095] This experiment was carried out with reference to the method proposed in the Chinese invention patent with authorization announcement number CN 112340730 B (invention name: A method for preparing a microporous carbon material based on carboxylation anchoring). This method proposes a method of using citric acid carboxylation to introduce carboxylic acid groups on the surface of the material, using alkali and carboxyl ion exchange to introduce alkali metals to the surface of the material, and fixing alkali metal ions at specific positions through the anchoring effect of carboxyl groups, and then melting metal ions through high-temperature activation, thereby achieving the purpose of making microporous carbon. However, the results of this experiment show that compared with the method of the present invention, the CK-CRH obtained in Experiment 6 has poor PX adsorption effect, and this method has a longer experimental cycle and uses more chemical reagents.

[0096] Experiment 7

[0097] This experiment replaces rice husks with shrimp and crab shells, aquatic waste, as biochar raw materials to explore the universality of the present invention, including the following steps:

[0098] (1) The purchased dried shrimp and crab shells were cleaned, dried, and crushed to obtain 80-mesh shrimp and crab shell powder (SS).

[0099] (2) 60 g of shrimp and crab shell powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution and stirred at room temperature for 2 h to remove calcium carbonate and inorganic impurities contained in the shrimp and crab shells. The material was then washed with water until neutral and then dried in a forced air drying oven at 80° C. After drying, shrimp and crab shell powder with inorganic impurities, pigments, and metal ions removed was obtained.

[0100] (3) The pretreated shrimp and crab shell powders were placed in an air dielectric barrier discharge (DBD) low temperature plasma (NTP) modification device, under an air relative humidity of 100%, with a discharge voltage of 40 V, a discharge current of 2.0 A, and a discharge time of 10 min. Through NTP treatment, shrimp and crab shell powders with etched surfaces and a large number of oxygen-containing groups (-COOH, -C=O, -OH) introduced into the surface were obtained.

[0101] (4) At a temperature of 80°C, 5 g of surface-modified shrimp and crab shell powder was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring effect of oxygen-containing groups. The material was then washed with water to remove excess alkali until it was neutral and dried in a forced air drying oven at 80°C.

[0102] (5) The dried shrimp and crab shell powder was placed in a tube furnace, heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 800 °C for 60 min for carbonization. After naturally cooling to room temperature, the obtained black highly hydrophobic microporous shrimp and crab shell carbon NTP-KC-SSC was obtained.

[0103] (6) At an ambient temperature of 30°C and an air relative humidity of 0%, 0.1g SSC, 0.1g NTP-SSC, 0.1g KC-SSC and 0.1g NTP-KC-SSC were placed in 650mL headspace bottles respectively with a concentration of 26.227mg / L of volatile organic gas PX as the target pollutant, and their removal rates of PX within 120min were observed. It was found that the adsorption effect reached a stable state at 60min, and the removal rate of PX by NTP-KC-SSC reached 91.3%, which was 58.8% higher than the adsorption rate of directly carbonized shrimp and crab shell charcoal (SSC) and 35.3% higher than the adsorption rate of shrimp and crab shell charcoal (KC-SSC) after only KOH ion exchange. Figure 4 shown.

[0104] Experiment 8

[0105] This experiment replaces rice husks with fruit shell waste grapefruit peels as biochar raw materials to explore the universality of the invention, including the following steps:

[0106] (1) The purchased dried grapefruit peel was pulverized to obtain grapefruit peel powder (PP) of 80 mesh.

[0107] (2) The pretreated grapefruit peel powder was placed in an air dielectric barrier discharge (DBD) low temperature plasma (NTP) modification device, under an air relative humidity of 100%, with a discharge voltage of 40 V, a discharge current of 2.0 A, and a discharge time of 10 min. Through NTP treatment, a grapefruit peel powder with an etched surface and a large number of oxygen-containing groups introduced on the surface was obtained.

[0108] (3) At a temperature of 80°C, 5 g of surface-modified grapefruit peel powder was immersed in 50 mL of 2 mol / L KOH solution for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring effect of oxygen-containing groups. The excess alkali was then removed by washing with water until it was neutral and dried in a forced air drying oven at 80°C.

[0109] (4) The dried grapefruit peel powder was placed in a tubular furnace and heated to 800 °C at a heating rate of 5 °C / min under a N2 atmosphere, and maintained at 900 °C for 60 min for carbonization. After naturally cooling to room temperature, the highly hydrophobic microporous grapefruit peel carbon NTP-KC-PPC was obtained.

[0110] (5) At an ambient temperature of 30°C and an air relative humidity of 0%, with a concentration of 26.227 mg / L of volatile organic gas PX as the target pollutant, 0.1 g PPC, 0.1 g NTP-PPC, 0.1 g KC-PPC, and 0.1 g NTP-KC-PPC were placed in 650 mL headspace bottles, and the removal rate of PX within 120 min was observed. It was found that the adsorption effect reached a stable state at 30 min, and the removal rate of PX by NTP-KC-PPC reached 85.2%, which was 55% higher than the adsorption rate of directly carbonized grapefruit peel charcoal (PPC) and 30% higher than the adsorption rate of grapefruit peel charcoal (KC-PPC) after only KOH ion exchange. The specific adsorption changes are as follows: Figure 5 shown.

[0111] Experiment 9

[0112] This experiment refers to Example 1, and the effect of ion exchange using different alkali metals (KOH, LiOH, NaOH) on the adsorption performance of the material after NTP modification includes the following steps:

[0113] (1) Crush rice husk to obtain 80-mesh rice husk powder.

[0114] (2) 60 g of rice husk powder was immersed in 250 mL of 1 mol / L hydrochloric acid solution, condensed and refluxed at 60° C. for 2 h, and then the material was washed with water until neutral, and then dried in a forced air drying oven at 80° C. After drying, rice husk powder with impurities, pigments, and metal ions removed was obtained.

[0115] (3) The pretreated rice husk powder was placed in an air dielectric barrier discharge (DBD) low-temperature plasma (NTP) modification device, under an environment of 100% relative air humidity, with a discharge voltage of 40 V, a discharge current of 2.0 A, and a discharge time of 10 min.

[0116] (4) At a temperature of 80°C, 5 g of the surface modified material was immersed in 50 mL of 2 mol / L LiOH, NaOH and KOH solutions for ion exchange for 60 min. The metal ions were evenly distributed on the surface of the material through the anchoring effect of the oxygen-containing groups. The material was then washed with water to remove excess alkali until it was neutral and dried in a forced air drying oven at 80°C.

[0117] (5) The dried material was placed in a tubular furnace and heated to 800°C at a heating rate of 5°C / min under a N2 atmosphere, and maintained at 800°C for 60 min for carbonization. After naturally cooling to room temperature, the final black highly hydrophobic microporous carbons NTP-LiC-CRH, NTP-NaC-CRH, and NTP-KC-CRH were obtained.

[0118] (6) At an ambient temperature of 30°C and an air relative humidity of 0%, the volatile organic gas PX with a concentration of 26.227 mg / L was used as the target pollutant. The above materials were placed in a 650 mL headspace bottle at a dosage of 0.1 g / L, and the removal rate of PX within 120 min was observed. It was found that the adsorption effect reached a stable state at 60 min. The removal rate of PX by NTP-LiC-CRH reached 69.8%, the adsorption rate of NTP-NaC-CRH was 90.8%, and the adsorption rate of NTP-KC-CRH was 98.4%. The specific adsorption changes are as follows: Figure 6 As shown, it can be seen that the adsorption performance is improved after alkali metal exchange, but KOH as the alkali source for alkali ion exchange has the best improvement on the adsorption effect. This is because the different activation strengths and ion sizes of alkali metal ions lead to different pore structures of biochar. The boiling points of lithium, potassium and sodium are 1340℃, 774℃ and 883℃ respectively. When the activation temperature reaches 800℃, only metallic potassium is reduced during the pyrolysis process and converted into highly diffuse potassium vapor, which can penetrate between the carbon lattice layers, inducing the expansion and disintegration of the carbon microstructure, thereby causing the carbon skeleton to expand and generate a microporous structure.

[0119] Experiment 10

[0120] In this experiment, referring to Example 1, the adsorption performance of different VOCs by NTP-KC-CRH was compared. At an ambient temperature of 30°C and a relative humidity of 0%, 20 μL of volatile organic gases, p-xylene, toluene, ethyl acetate, n-hexane, and dimethyl disulfide, were used as target pollutants in a 650 mL headspace bottle. The adsorbent was 0.1 g of NTP-KC-CRH. The adsorption was investigated within 120 min. Figure 7 As shown, the adsorption rate of p-xylene is stable at 98.4%, the adsorption rate of toluene is 80.0%, the adsorption rate of ethyl acetate is 71.7%, the adsorption rate of n-hexane is 74.5%, and the adsorption rate of dimethyl disulfide is 91.4%. The molecular diameters of different gas adsorbents are different, resulting in different adsorption effects. It can be seen that this adsorbent is suitable for adsorbing a variety of VOCs.

[0121] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing highly hydrophobic microporous carbon by low-temperature plasma anchoring oxygen-containing functional groups assisted by ion exchange, characterized in that: include: (1) treating the biocarbon source with low-temperature plasma to obtain a surface-modified material; (2) mixing the surface modification material with an alkali metal hydroxide to obtain an alkali metal-surface modification material; (3) subjecting the alkali metal-surface modified material to high temperature carbonization treatment at 800-1000°C; The low temperature plasma treatment comprises: The biocarbon source is treated with low-temperature plasma in an air atmosphere at a voltage of 30 to 60 kV.

2. The method according to claim 1, characterized in that: The low temperature plasma treatment time is 5 to 25 minutes.

3. The method according to claim 1, characterized in that The relative humidity of the low temperature plasma treatment is 50% to 100%.

4. The method according to claim 1, characterized in that The discharge current of the low-temperature plasma treatment is 2.0-2.3A.

5. The method according to claim 1, characterized in that The alkali metal oxide is mixed with the surface modification material in the form of a solution for 0.5 to 2.5 hours.

6. The method according to claim 1, characterized in that In the alkali metal oxide solution, the concentration of the alkali metal oxide is 0.5-2 mol / L.

7. The method according to claim 1, characterized in that The material-liquid ratio of the surface modification material to the alkali metal oxide solution is 1:(10-15) g / ml.

8. The method according to claim 1, characterized in that The alkali metal hydroxide is one or more of KOH, NaOH, LiOH and CsOH.

9. The method according to claim 1, characterized in that: The high temperature carbonization treatment comprises: In a N2 atmosphere, the temperature was raised to 800-1000°C at a heating rate of 5°C / min and maintained at 800-1000°C for 60-80 min.

10. Highly hydrophobic microporous carbon prepared by the method according to any one of claims 1 to 9.